2020
DOI: 10.1016/j.brainres.2020.146712
|View full text |Cite
|
Sign up to set email alerts
|

Muscular effort coding in action representation in ballet dancers and controls: Electrophysiological evidence

Abstract: Dancers and controls were shown technical ballet gestures during EEG recording.• Effortful and effortless movements were compared. • Effortful steps elicited a larger P300 and parietal LP (late positivity) in dancers.• Visuomotor regions were more active in dancers than controls in LP time window. • Expertise was required for an automatic and more refined coding of muscular effort. A R T I C L E I N F O A B S T R A C TThe present electrophysiological (EEG) study investigated the neural correlates of perceiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 114 publications
(148 reference statements)
2
8
0
Order By: Relevance
“…If KMI requires the engagement of visuomotor processes, ballet dancers should be able to recall sensorimotor representations due to their extensive training (larger AN). They were also expected to encode effort information during movement observation (Orlandi et al, 2020), consistent with previous evidence on professional musicians (vs. controls; Pau et al, 2013). In contrast, MI of effortful (vs. effortless) movements would result in enhanced cognitive demands (larger AN) in controls lacking in specific motor expertise with ballet, due to increased effortrelated kinematic information (Proverbio et al, 2009).…”
Section: Text 1 Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…If KMI requires the engagement of visuomotor processes, ballet dancers should be able to recall sensorimotor representations due to their extensive training (larger AN). They were also expected to encode effort information during movement observation (Orlandi et al, 2020), consistent with previous evidence on professional musicians (vs. controls; Pau et al, 2013). In contrast, MI of effortful (vs. effortless) movements would result in enhanced cognitive demands (larger AN) in controls lacking in specific motor expertise with ballet, due to increased effortrelated kinematic information (Proverbio et al, 2009).…”
Section: Text 1 Introductionsupporting
confidence: 78%
“…Since the partial functional overlap between the neural substrates that underlie MI and motor planning (Hardwick et al, 2017;Jeannerod, 1994;2001), we interpreted the present findings consistent with Pau's study. In a previous paper (Orlandi et al, 2020), we reported evidence of increased frontoparietal activity (larger frontal P300 and parietal Late Positivity components) during the observation of the effortful (vs. effortless) dance movements (used in the present study) in ballet dancers (vs. controls). It is, therefore, possible that effort information has been efficiently processed by dancers while observing the actions, resulting in reduced cognitive demands (smaller AN to effortful vs. effortless movements)…”
Section: Discussionsupporting
confidence: 54%
“…In (Orlandi et al, 2020b), when dancers and non-dancer controls observed "effortful" ballet steps: both groups had a greater late positivity effect in posterior regions than when they observed and "effortless" ones; frontoparietal regions were more engaged in dancers and occipitotemporal regions were more engaged in controls. A larger P300 was observed in the frontal regions of dancers when they observed effortful movements than in the controls.…”
Section: Brain Wave Activitymentioning
confidence: 80%
“…Many components of the neuroscience of dance observation appear to be affected by dance training, including corticospinal excitability (Jola et al, 2012), and brain wave activity (Di Nota et al, 2017;Orgs et al, 2008;Poikonen et al, 2018aPoikonen et al, , 2018b. Dancers also appear to have faster processing and subsequent recognition of dance, with enhanced visuo-motor resonance processes, and refined action processing (Orlandi and Proverbio, 2019;Orlandi et al, 2017Orlandi et al, , 2020b.…”
Section: Observationmentioning
confidence: 99%
“…Cortical activation levels might indicate amount of depicted motion perceivers report, and impressions of the perceived position of stationary objects ( Pinna and Brelstaff, 2000 ; Pavan et al, 2011 ). A cortical AON or action observation network is thought to be triggered by static images and might be related to the observer’s own skills ( Orlandi et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%